Embracing Possibility: A Playful Attitude Towards the Creation of Playful Objects - Gavin, Jenna (Auckland University of Technology, 2015)
This exegesis documents a sketch-based methodology to explore ludic creation, expression and experience. Sketched artefacts of ludic expression and ludic experience are positioned within two frameworks: 1) the Absurd, signifying a rebellious embrace of a chaotic world; 2) the Database, a new media structure for collecting, thinking and producing. Linked by the themes of possibility and meaning, these two frameworks uphold a tension between exploration and order, presenting a post-disciplinary approach to creation. Design research permits a practical and theoretical investigation into ludic creation and experience. The making of sketch-based artefacts generates new knowledge, bringing to light the notion of a playful and interactive absurd sensibility. The artefacts demonstrate the possibility at the core of creativity and the game medium. They also demonstrate a personal and emotive approach to game design. This research puts forward an alternative perspective from which to view the ludic sphere and the practice of game design.
Keywords: Game design; Creativity; Absurd; Database; Design research; Sketching